Circulating "LncPPARδ" From Monocytes as a Novel Biomarker for Coronary Artery Diseases. Issue 6 (February 2016) - Cai, Yue; Yang, Yujia; Chen, Xiongwen; He, Duofeng; Zhang, Xiaoqun; Wen, Xiulan; Hu, Jiayong; Fu, Chunjiang; Qiu, Dongfeng; Jose, Pedro A.; Zeng, Chunyu; Zhou, Lin
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: To investigate long noncoding RNA NONHSAT112178 (LncPPARδ) as a biomarker for coronary artery disease (CAD) in peripheral blood monocyte cells, RT-qPCR was performed to validate the microarray results, receiver operating characteristic curve was applied to study the potential of LncPPARδ as a biomarker. Diagnostic models from LncPPARδ alone or combination of risk factors were constructed by Fisher criteria. The expression of genes neighboring the LncPPARδ gene was examined with RT-qPCR in THP-1 cell line treated with LncPPARδ siRNA. Using a diagnostic model by Fisher criteria, the consideration of risk factors increased the optimal sensitivity from 70.00% to 82.00% and decreased the specificity from 94.00% to 78.00%. The consideration of risk factors also increased area under the receiver operating characteristic curve from 0.727 to 0.785 ( P  = 0.001), from 0.712 to 0.768 ( P  = 0.01), and from 0.769 to 0.835 ( P  = 0.07), in the original, training, and test sets, respectively. Finally, we found that the expression of peroxisome proliferator-activated receptor δ (PPARδ), Adipose Differentiation-Related Protein (ADRP), and Angiopoietin-like 4 (ANGPTL4) were affected by LncPPARδ silencing. Our present study indicated that LncPPARδ, especially combined with risk factors, can be a good biomarker for CAD. LncPPARδ regulates the expression of neighboring protein-coding genes, PPARδ and its direct target genes ADRP and ANGPTL4.